A Resource-Efficient, High-Dose, Gamified Neurorehabilitation Program for Chronic Stroke at Home: Retrospective Real-World Analysis - Spencer A Arbuckle; Anna Sophie Knill; Michelle H Chan-Cortés; Gabriela Rozanski; Anastasia Elena Ford; Louis T Derungs; John W Krakauer; Naveed Ejaz; David Putrino; Jenna Tosto-Mancuso; Meret Branscheidt (JMIR Serious Games)
Abstract BackgroundAccumulating evidence and medical guidelines recommend high-dose neurorehabilitation for recovery after stroke. The reality, however, is that most patients receive a fraction of this dose, with therapist availability and costs of delivery being major implementational barriers. ObjectiveThis study aimed to explore a potential solution by conducting a retrospective analysis of a real-world enhanced clinical service that used gamified self-training technologies at home under remote therapist supervision. MethodsData from 17 patients who completed a 12‐18 week full-body, high-dose neurorehabilitation program entirely at home were analyzed. Program delivery relied primarily on patients training independently (asynchronously) with the MindMotion GO (MindMaze) gamified-therapy solution. Accompanying telerehabilitation training sessions with a therapist occurred weekly while therapists used a web application to continuously monitor and manage the program remotely. Effectiveness of the program was assessed through measured active training time, a measure that more closely reflects delivered dosage as opposed to scheduled dose. Patient recovery was evaluated with standardized impairment and functional clinical measures and patient self-reported outcome measures. Finally, a cost model was computed to evaluate the resource efficiency of the program. ResultsPatients maintained high training adherence throughout the program and reached an average total active training time of 39.7 (SD 21.4) hours, with the majority delivered asynchronously (mean 82.2%, SD 10.8%). Patients improved in both upper-limb (Fugl-Meyer Upper Extremity, mean 6.4, SD 5.1; PPP ConclusionsThis work demonstrates effective high-dose neurorehabilitation delivery via gamified therapy technologies at home. The approach shows that training time can be successfully decoupled from therapist-presence without compromising adherence, outcomes, or patient satisfaction over an extended program period. Given growing concerns over therapist availability and increasing health care costs, this resource-efficient approach can help achieve medical guidelines and complement existing clinic-based approaches.